A Fox and a Weasel (Hor. Epist. 1. 7. 29–36) - Novikova, Alexandra (Hyperboreus, 2017)
The article discusses Hor. Epist. 1. 7. 29–33, with a version of an Aesopian fable. These verses are notoriously difﬁcult. They describe a fox that crawls into a basket of corn (cumera frumenti), cannot climb out because it has eaten too much food, and is laughed at by a weasel; this surprisingly appears to mean that the fox feeds on corn. The author argues that, contrary to the prevailing opinion, Horace should not be charged with zoological ignorance or with poetic disregard of zoological facts; nor are Bentley’s famous emendation to nitedula instead of vulpecula or some manuscripts’ reading camera instead of cumera acceptable. The data of the lexica shows that cumera designates not a small basket, but a voluminous twiggen or ceramic vessel with a lid for grain; the fox climbs into it and eats several mice, not corn.The meaning of the fable in the context of Horace’s Letter to Maecenas is further revisited: the v. 34 Hac ego si compellor imagine, cuncta resigno is often taken to mean that the poet is ready to give Maecenas back everything that he got from him, fearing the fortune of the fox; however, this does not ﬁt the poet’s conduct; moreover, in this understanding, resigno is in the conjunctive, not the indicative case. Rather, the verse means that the poet, although desiring to please Maecenas and to come to Rome, remains in the countryside and thus abandons all eventual goods of life under Maecenas’ tutelage, because he duly applies to himself compellare in the reﬂexive meaning) the example of the stuffed fox.